BIOELECTRICAL IMPEDANCE ANALYSIS OF BODY COMPOSITION IN FITNESS AND BODYBUILDING COMPETITORS AND RECREATIONAL EXERCISERS - Gligoroski, Adam; Zivkovic , Vujica; Todorovic, Miodrag; Aleksovska Velichkovska Lenche, Lenche (Sanamed, 2024)
Introduction: Bodybuilding and fitness are sports in which the primary goal is to build and shape a desirable body figure. Consequently, achieving the ideal body composition is the ultimate aspiration of every participant in these sports. Body composition analysis is a valuable tool for assessing body structure and quantifying data for this specific athletic population. The aim of this study was to determine and compare the body composition characteristics of fitness and bodybuilding enthusiasts, both competitive and recreational. Material and Methods: This study included 89 adult women and men, aged 18 to 37, who were categorized into four groups: female competitors (N=9), female recreational participants (N=30), male competitors (N=15), and male recreational participants (N=35). Body composition was assessed using the bioelectrical impedance method, specifically the InBody720. Results: The comparison of bioelectrical impedance analysis (BIA) obesity parameters revealed that BMI did not significantly differ between competitors and recreational participants in both male and female groups. However, competitors (both male and female) displayed a higher volume of body fluids (ICW and ECW). Body fat mass (BFM) was statistically greater in recreational participants when compared to competitors, with females having 18.58 kg vs. 12.47 kg, and males having 16.64 kg vs. 9.81 kg. Mean values of body fat percentage were also statistically higher in recreational participants compared to competitors, with women at 27.25% vs. 16.39% and men at 19.49% vs. 11.97%.Conclusions: Fitness competitors had a significantly higher fat-free mass and a significantly lower fat component. Recreational exercisers exhibited significantly higher obesity parameters, body fat percentage, and waist-to-hip ratio (WHR) compared to competitors in fitness and bodybuilding.
Keywords: bodybuilding; body fat mass; competitors; fitness; recreational; skeletal muscle mass